THE EFFECTIVENESS OF USING CAKE APPLICATION ON STUDENTS' PRONUNCIATION SKILLS AT SMP UNISMUH MAKASSAR - Hermawati, Sri; Bte Abdul, Nurdevi; AM, St. Asmayanti (English Language Teaching Methodology, 2023)
This study aims to find out the use of Cake Application in improving the students' pronunciation skills at the nine grade of SMP Unismuh Makassar.This research used quantitative research with a pre-experimental approach. The researcher gave pre-test to the students, and then the researcher gave the students’ treatment using Cake Application. After giving treatment, researcher gave post-test to the students. The population in this study were students of the class IX SMP Unismuh Makassar. The sample of this research was the students of the class IX.A, included 33 students.The result showed that the t-test value was higher than t-table value. The t-test value of pronunciation is greater than t-table (8.21>2.03693). It was concluded that the null hypothesis (H0) was rejected and the alternative hypothesis (H1) was accepted. That means there were significant differences students' pronounciation skill before and after using the Cake Application. The research conducted shows that the use of Cake Application on students’ pronunciation skills was effective.